TA’ARUF PHENOMENON THROUGH MARRIAGE IN PEKANBARU (Study Phenomenology In Kader PKS) - Rizqa Hidayati; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Recently, the phenomenon of ta'aruf marriage has become familiar in our society, especially among public figures such as artists already doing ta'aruf marriage. In the city of Pekanbaru wedding ta'aruf by Moslems also become a phenomenon in which there is an increase in terms of implementation. It can be seen from the cadre of Partai Keadilan Sejaktera (PKS) are about to get married. Ta'aruf wedding process does not occur in the other party cadres. This study aims to determine the motives, meanings and communication experience PKS cadres who were married through ta'aruf process..This study uses qualitative research with phenomenological approach. Informants in this study were five cadres who were married through ta'aruf process, Using a snowball sampling technique.. Data was collected techniques is done by participant observation, interview, and documentation. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation.Results from this study showed that the motives of the PKS cadres. Motifs past (Because motif) form of theological motifs, basis of religion because of the theological motifs that have been ingrained in them, a commitment to build a vision of building a wedding, and believe the mediator Yag get to know potential mates. While the motive of the future (in-order to) is the desire to be happy family, mawaddah and Rohmah, cultivate relationships syar'i, keingianan have children pious and courtship after marriage. Making of PKS cadres do ta'aruf marriage is a doctrine as the implementation of Islamic Shari'a, as a media partner and as an exploration of psychological needs and social control Communication experience PKS cadres do ta'aruf marriage is a pleasant communication experience includes; the pair know each other from time to time, received the partner's family, and established cooperation with the community, while not pleasant communication experience includes; busyness couples, families and relatives of opposition parties, and the stigma of people who said marriage ta'aruf like buying a cat in a sack.Keyword: phenomenon, marriage ta’aruf, motive, meaning, communication experienceJOM